Increasing Trend of Mergers and its Impact on the Bottom Line: Evidence from Pakistan’s Banking Sector - Muzzamil Hussain; Muhammad Mubeen (SEISENSE (PRIVATE) LIMITED, 2018)
Aim of this study is to provide the information to the bankers, government authorities, employees and the investor of the financial institutions about the impact of the merger on the performance of the banks. For this purpose, financial ratios such as the liquidity ratio, loan to deposit ratios are measured to see the short term paying capacity of the banks. Investment ratio such as earning asset to total asset ratio; solvency ratio such as “deposit time capital”; equity capital to total asset, profitability ratios include the interest margin to earning asset are used to analyze the impact of merger and on bank performance. By using ratio analysis, the study concludes if the merger and have a positive relationship with merger.